Analysis of Accounting Information System Implementation in Government Service Units: A Case Study of Dual Financial Recording Systems - Asriani Natong (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This study aims to analyze the implementation of Accounting Information Systems (AIS) in public service units, with a specific focus on the phenomenon of a dual recording system that combines manual methods with simple digital applications such as Microsoft Excel. A qualitative descriptive approach with a case study method was employed. Data were collected through in-depth interviews with financial staff and heads of public service units, non-participant observation, and analysis of financial documents from two government units: a Community Health Center (Puskesmas) and a District Education Office unit. The findings reveal that government units operate in a transitional phase of financial digitalization, adopting a hybrid system due to factors of digital literacy gaps, risk management considerations, cost-benefit analysis, and ingrained bureaucratic work culture. This dual practice enhances control efficiency and accelerates access to financial information, thereby supporting more transparent and accountable reporting. However, it remains vulnerable to risks of data duplication errors, overlooked transactions, and over-reliance on operator integrity. The study elaborates extensively on the daily workflow of the dual system, the motivations behind its persistence, and its nuanced implications. The research concludes that successful AIS implementation in government units requires a phased, context-sensitive approach that integrates technology adoption with human resource capacity building and strengthening of internal controls.